Impact of Implementing the 2013 ACC/AHA Cholesterol Guidelines on Vascular Events in a Statewide Community‐Based Practice Registry. Issue 7 (26th November 2015) - Egan, Brent M.; Li, Jiexiang; Fleming, Douglas O.; White, Kellee; Connell, Kenneth; Davis, Robert A.; Sinopoli, Angelo
Abstract : Electronic health record data were analyzed to estimate the number of statin‐eligible adults with the 2013 American College of Cardiology/American Heart Association cholesterol guidelines not taking statin therapy and the impact of recommended statin therapy on 10‐year atherosclerotic cardiovascular disease (ASCVD10 ) events. Adults aged 21 to 80 years in an outpatient network with ≥1 clinic visit(s) from January 2011 to June 2014 with data to calculate ASCVD10 were eligible. Moderate‐intensity statin therapy was assumed to lower low‐density lipoprotein cholesterol by 30% and high‐intensity therapy was assumed to reduce low‐density lipoprotein cholesterol by 50%. ASCVD events were assumed to decline 22% for each 39 mg/dL decline in low‐density lipoprotein cholesterol. Among 411, 768 adults, 260, 434 (63.2%) were not taking statins and 103, 478 (39.7%) were eligible for a statin, including 79, 069 (76.4%) patients with hypertension. Estimated ASCVD10 events were 18, 781 without and 13, 328 with statin therapy, a 29.0% relative and 5.3% absolute risk reduction with a number needed to treat of 19. The 2013 cholesterol guidelines are a relatively efficient approach to reducing ASCVD in untreated, statin‐eligible adults who often have concomitant hypertension.